The Lima reader history, culture, politics - Aguirre, Carlos 1958-; Walker, Charles F. 1959- (Duke University Press, 2017)
Pre-Hispanic, conquest, and early Colonial Lima -- Pre-Hispanic Lima / César Pacheco Vélez -- The foundation of Lima / Garcilaso de la Vega, el Inca -- The form and greatness of Lima / Bernabé Cobo -- Lima's convents / José de la Riva-Aguero -- The spiritual diary of an Afro-Peruvian mystic / Ursula de Jesús -- Auto-da-fé and processión / Josephe and Francisco Mugaburu -- Margarita's wedding dress / Ricardo Palma -- Bourbon Lima -- Of the inhabitants of Lima / Jorge Juan and Antonio de Ulloa -- The 1746 earthquake / Anonymous -- A failed Indian uprising / Anonymous -- Lima and Cuzco / Concolorcorvo -- Slave religion and culture / Hesperióphylo -- Faces of all colors / Hipólito Ruiz -- Impressions of Lima / Alexander von Humboldt -- From independence to the War of the Pacific (1821-1884) -- Lima in 1821 / Basil Hall -- The passion for bullfighting / William S. W. Ruschenberger -- Pancho Fierro / Natalia Majluf -- A slave plantation / Flora Tristán --
Includes bibliographical references and index. - Description based on print version record
Keywords: Geschichte; Kultur; Lima